Lógica deôntica: os paradoxos deônticos e as practições em Castaneda - Barros, Toni Cézar Pinto Ferreira (2014)
There are two questions about deontic logic that appear frequently in the literature on the subject. The first concerns the legitimacy and the second the deontic paradoxes. The first of these, however, is not the main concern of this paper, we assume, alongside Castañeda the thesis that there are logical relationships, not only between propositions, but also among imperatives and norms. Thus, the main focus of this paper will be to investigate deontic paradoxes, and in particular, the Castañeda‟s solution. This solution involves a distinction between propositions and practitions as well as between imperatives and norms. We also show the advantage of this solution compared to other solution named scope deontic operator. Finally, we analyze Lou Goble‟s criticism to Castañeda‟s solution and objections to this criticism.